Predicting the dominating factors during heat transfer in magnetocaloric composite wires. (August 2020) - Krautz, Maria; Beyer, Lukas; Funk, Alexander; Waske, Anja; Weise, Bruno; Freudenberger, Jens; Gottschall, Tino
Abstract: Magnetocaloric composite wires have been studied by pulsed-field measurements up to μ 0 Δ H = 10 T with a typical rise time of 13 ms in order to evaluate the evolution of the adiabatic temperature change of the core, Δ T ad, and to determine the effective temperature change at the surrounding steel jacket, Δ T eff, during the field pulse. An inverse thermal hysteresis is observed for Δ T ad due to the delayed thermal transfer. By numerical simulations of application-relevant sinusoidal magnetic field profiles, it can be stated that for field-frequencies of up to two field cycles per second heat can be efficiently transferred from the core to the outside of the jacket. In addition, intense numerical simulations of the temperature change of the core and jacket were performed by varying different parameters, such as frequency, heat capacity, thermal conductivity and interface resistance in order to shed light on their impact on Δ T eff at the outside of the jacket in comparison to Δ T ad provided by the core. Graphical abstract: Unlabelled Image Highlights: simultaneous monitoring of magnetic-field induced temperature change of magnetocaloric core and surrounding steel jacket 75% of the intrinsic ∆ T ad in La(Fe, Co, Si)13 can be used directly as ∆ T eff at the jacket for field-frequencies of <2Hz inverse thermal hysteresis of the core temperature change observed for field frequencies >10Hz numerical simulations provide guidelines for the best choice of material combination in magnetocaloric composite wires